道教“幸福观”研究(以《太平经》为主要文本）= A study of taoism’s “View of Happiness” (using “Tai-Ping Jing” as main text) - 伍凤燕 Ng, Feng Yan (2009)
从古至今，人活在世上都是以追求“幸福”为目标，无论是古代中国的思想家或是宗教都视“幸福”为一项极为重要的课题。本论文的开始将以比较儒家与道家的思想，从中得出中国古代思想家的“幸福观”。道教是中国土生土长的宗教，也是中国文化的重要组成部分，因此若要了解中国的思想，道教也是个不可或缺的研究对象。本论文将以代表道教初期的经典《太平经》为主要文本，深入探讨道教如何以其“生命观”与“死亡观”，建构出其“幸福观”。然后将会以从道家演变成道教，一种学术思想向宗教思想的演变之中，对“幸福”这个课题的差异来总结出幸福与宗教的关系。本论文希望通过这项研究，给人们一些启发，让人们对幸福与宗教的关系有更进一步的了解与体会，因此而找到其幸福的独特途径。This thesis is a study of “Happiness” in Taoism’s ideology. From the ancient times, “Happiness” is always an essential issue in everyone’s daily life, particularly in the works of Chinese philosophers and religions. This thesis will start with the comparison between Confucianist and Taoist philosophies to derive the ancient Chinese philosophers’ views of “Happiness”. Since Taoism is an indigenous religion of China, it is also an inevitable research subject in order to understand ancient Chinese’s philosopy. The representative material of early Taoism, “Tai Ping Jing” will be the main text for this study, focusing on the view of “Life” and “Death” and in turn developing the view of “Happiness”. To conclude this thesis, a comparison of the views of “Happiness” between the Taoist philosophy and Taoism was done to bring out the reason behind the development of a philosophy to a religion, from there deriving the relationship between “Happiness” and religion. From the result of this study, individuals can discover their own unique way to achieve true happiness.